Performance of natural-dye-sensitized solar cells by ZnO nanorod and nanowall enhanced photoelectrodes - Saadaoui, Saif; Ben Youssef, Mohamed Aziz; Ben Karoui, Moufida; Gharbi, Rached; Smecca, Emanuele; Strano, Vincenzina; Mirabella, Salvo; Alberti, Alessandra; Puglisi, Rosaria A. (Beilstein Journal of Nanotechnology, 2017)
In this work, two natural dyes extracted from henna and mallow plants with a maximum absorbance at 665 nm were studied and used as sensitizers in the fabrication of dye-sensitized solar cells (DSSCs). Fourier transform infrared (FTIR) spectra of the extract revealed the presence of anchoring groups and coloring constituents. Two different structures were prepared by chemical bath deposition (CBD) using zinc oxide (ZnO) layers to obtain ZnO nanowall (NW) or nanorod (NR) layers employed as a thin film at the photoanode side of the DSSC. The ZnO layers were annealed at different temperatures under various gas sources. Indeed, the forming gas (FG) (N2/H2 95:5) was found to enhance the conductivity by a factor of 103 compared to nitrogen (N2) or oxygen (O2) annealing gas. The NR width varied between 40 and 100 nm and the length from 500 to 1000 nm, depending on the growth time. The obtained NWs had a length of 850 nm. The properties of the developed ZnO NW and NR layers with different thicknesses and their effect on the photovoltaic parameters were studied. An internal coverage of the ZnO NWs was also applied by the deposition of a thin TiO2 layer by reactive sputtering to improve the cell performance. The application of this layer increased the overall short circuit current Jsc by seven times from 2.45 × 10−3 mA/cm2 to 1.70 × 10−2 mA /cm2.
Keywords: DSSCs; I–V measurement; nanorods; nanowalls; natural dye; ZnO